The contribution of women's participating in economic development activities: A case of Mkolani ward in Nyamagana District Mwanza - Msangi, Mariam Hassan (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfilment of the requirements for the award of the degree of Masters of Business Administration in Corporate Management (MBA-CM) of Mzumbe University.